Twisted Python : the engine of your Internet - McKellar, Jessica (O'Reilly Media, 2014)
"How do you write and deploy extensible, testable, cross-platform clients and servers for your favorite network protocols? With Twisted!Twisted is an event-driven Python networking library with off-the-shelf client and server implementations for protocols like HTTP, IMAP, SSH, FTP, IRC, and more.In this hands-on webcast presented by Jessica McKellar author of Twisted, she gives an architectural overview of the project and then dive in to what you need to know to build robust clients and servers for popular and custom network protocols, including: The Deferred API for managing reactions to asynchronous eventsTransports, protocols, and writing basic clients and serversTwisted's plugin and deployment infrastructureBy the end of this webcast, you'll be well-versed in Twisted's philosophy and the event-driven programming model and know how to structure, deploy, and test Twisted clients and servers for any network protocol."--Resource description page.